Investigation of the Usability of Recycled Aggregate Obtained from Post-Earthquake Building Demolition Wastes on Highways: An Evaluation for Turkey - Akpınar, Gökhan; Yılmaz, Mehmet (Avestia Publishing, 2025)
It should be kept in mind that natural resources in our world are not infinite and will one day be exhausted if not used carefully. Increasing consumption in parallel with population growth and the uncontrolled release of wastes resulting from this consumption into nature disrupt the ecological balance and damage the nature. Wastes that can be recycled can be recycled through various physical or chemical processes. In this way, it is ensured that both natural resources are protected and waste materials with economic value are brought to the economy. In many developed countries, legal regulations have been introduced that encourage the recycling of waste materials and prohibit the disposal of recyclable materials. Developing countries, which are striving for development and facing economic difficulties, also need to put an end to waste waste in order to utilize natural resources efficiently and protect their natural resources. For this reason, waste materials with economic value should be recycled and reused. In disasters such as earthquakes, if the damage and impact are large, a significant amount and volume of disaster waste is generated. After the earthquakes that occurred in our country on February 6, 2023, within the scope of damage assessment studies carried out by the MoEU in 13 provinces, it was determined that 263,800 independent units in 61,722 buildings were in need of urgent demolition, heavily damaged and demolished as of February 16, 2023. Accordingly, the amount of earthquake waste was preliminarily calculated and the estimated amount of waste to be generated on a provincial basis was calculated. The total amount of earthquake wastes is estimated to be between ~50 million tons and ~110 million tons. Earthquake wastes should be transported to temporary storage areas, where the materials in the wastes should be separated and reused, recycled/recycled/recycled to a large extent, and the remaining wastes should be disposed of within the framework of the provisions specified in the relevant regulations according to their hazardousness level. © 2025, Avestia Publishing. All rights reserved.
10th World Congress on Civil, Structural, and Environmental Engineering, CSEE 2025 -- 10 April 2025 through 12 April 2025 -- Barcelona -- 330019
Keywords: Construction Demolition Waste; Earthquake; Hot mix asphalt; recycled aggregate